EVALUASI MUTU BETON BANGUNAN PERTASHOP DI WILAYAH WONOGIRI BERDASARKAN UJI SERTIFIKAT LAIK FUNGSI (SLF) METODE CONCRETE HAMMER TEST - ristanto, iwan; Agung Wibawa, Satria (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
This study aims to evaluate the concrete quality of Pertashop buildings in Wonogiri Regency based on compressive strength results using the Concrete Hammer Test method (SNI 03-4430-1997). Building Approval or Persetujuan Bangunan Gedung (PBG) as well as Certification of Functionality (SLF) during the period from January to March 2024 with a total of 10 Pertashops in all areas of Wonogiri Regency with a test area of ​​9 test areas that were 28 days old. Each area was tested with 10 shots. The purpose of this study was to determine the quality results of the concrete structure quality of the Pertashop building in Wonogiri Regency based on the value of the hammer test compressive strength factor. From the results of concrete testing on the Pertashop building in Wonogiri Regency by taking samples of 10 points of the Pertashop location where it was built, it can be concluded that the Pertashop machine seat floor has a better concrete quality than K.225kg/cm2, while the Pertashop yard floor and Pertashop column pillars are still below the quality of K.225kg/cm2. Statistical tests in scatter-plots whose data comes from samples that are normally distributed multivariate, conclude that the quality of the Pertashop machine seat concrete plate H0 is rejected or data from two variables (Quality of floor slab concrete and column concrete).